2015
DOI: 10.1021/acs.chemrestox.5b00283
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and Adaptive Stress Responses to Selected Haloacetic Acid and Halobenzoquinone Water Disinfection Byproducts

Abstract: The process of disinfecting drinking water inadvertently leads to the formation of numerous disinfection byproducts (DBPs). Some of these are mutagenic, genotoxic, teratogenic, and cytotoxic, as well as potentially carcinogenic both in vivo and in vitro. We investigated the in vitro biological activity of five DBPs: three monohaloacetic acids (monoHAAs) [chloroacetic acid (CAA), bromoacetic acid (BAA), and iodoacetic acid (IAA)] and two novel halobenzoquinones (HBQs) [2,6-dichloro-p-benzoquinone (DCBQ) and 2,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 71 publications
3
49
0
Order By: Relevance
“…Electrophilic chemicals and chemicals that produce reactive oxygen species can induce the oxidative stress response as the presence of these chemicals releases transcription factor Nrf2 from negative regulator Keap1, which in turn activates the antioxidant response element (Zhang 2006). Environmental water samples (Escher et al 2012), micropollutants (Martin et al 2010, Escher et al 2013 and DBPs (Procházka et al 2015, Stalter et al 2016a) have been shown to activate the oxidative stress response, with 23% of analysed chemicals in the US EPA ToxCast database reported to induce oxidative stress (US EPA 2015). The p53 transcription factor responds to DNA damage and will initiate repair proteins, alter the cell cycle or induce apoptosis (Knight et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Electrophilic chemicals and chemicals that produce reactive oxygen species can induce the oxidative stress response as the presence of these chemicals releases transcription factor Nrf2 from negative regulator Keap1, which in turn activates the antioxidant response element (Zhang 2006). Environmental water samples (Escher et al 2012), micropollutants (Martin et al 2010, Escher et al 2013 and DBPs (Procházka et al 2015, Stalter et al 2016a) have been shown to activate the oxidative stress response, with 23% of analysed chemicals in the US EPA ToxCast database reported to induce oxidative stress (US EPA 2015). The p53 transcription factor responds to DNA damage and will initiate repair proteins, alter the cell cycle or induce apoptosis (Knight et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The p53 transcription factor responds to DNA damage and will initiate repair proteins, alter the cell cycle or induce apoptosis (Knight et al 2009). The p53 response assay can detect genotoxic compounds and has previously been applied to individual DBPs (Procházka et al 2015, Stalter et al 2016a) and water samples (Yeh et al 2014, Neale et al 2015a. NF-κB is an important transcription factor associated…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are growing concerns regarding potential epigenetic, cytotoxic and genotoxic effects of compounds formed by consumer products such as halobenzoquinones . These compounds, which are not typical found in drinking water, may affect neural stem cells (Fu et al, 2017;Procházka et al, 2015;. In addition, natural humic substances as well as consumer products may generate DBPs with endocrine disrupting activities (Itoh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%